Intraoperative visualisation and treatment of salivary glands in Sjögren’s syndrome by contrast-enhanced ultrasound sialendoscopy (CEUSS): protocol for a phase I single-centre, single-arm, exploratory study - Arjan Vissink; K Hakki Karagozoglu; Tim Forouzanfar; Henk S Brand; Derk Hendrik Jan Jager; Marco Helder; Joseph Bot; Otto Kamp; Seunghee Cha; Gary Weisman; Imke Bartelink (BMJ Open)
Introduction We established a promising sialendoscopic treatment for in vivo enhancement of salivation in salivary glands affected by Sjögren’s syndrome (SS). In this technique, the ducts of the salivary glands are irrigated with saline and steroids. This allows for dilatation of ductal strictures and removal of debris. Unfortunately, it is not possible to assess the delivery and penetration of saline or medications in the ductal system and parenchyma. To address this problem, we will conduct contrast-enhanced ultrasound sialendoscopy (CEUSS) using sulphur hexafluoride microbubbles. To the best of our knowledge, microbubbles have never been used for the treatment of salivary glands in SS. It is, therefore, imperative to test this application for its safety and feasibility.Methods and analysis A single-arm phase I study will be performed in 10 SS patients. Under local anaesthesia, ultrasound (US) guided infusion of the parotid and submandibular glands with microbubbles will be performed. Continuous US imaging will be used to visualise the glands, including the location of strictures and occlusions. Main outcomes will be the evaluation of safety and technical feasibility of the experimental treatment. Secondary outcomes will consist of determinations of unstimulated whole mouth saliva flow, stimulated whole mouth saliva flow, stimulated parotid saliva flow, clinical oral dryness, reported pain, xerostomia, disease activity, salivary cytokine profiles and clinical SS symptoms. Finally, salivary gland topographical alterations will be evaluated by US.Ethics and dissemination Ethical approval for this study was obtained from the Medical Ethics Committee of the Amsterdam University Medical Centre, Amsterdam, The Netherlands (NL68283.029.19). data will be presented at national and international conferences and published in a peer-reviewed journal. The study will be implemented and reported in line with the Standard Protocol Items: Recommendations for Interventional Trials’ statement.Trial registration numbers The Netherlands Trial Register: NL7731, MREC Trial Register: NL68283.029.19; Pre-results.